Використання методів штучного інтелекту для управління кліматичними системами в закритому агровиробництві - Шеліхов, Ю. О.; Аксак, Н. Г. (ХНУРЕ, 2025)
The purpose of this study is to implement climate control systems in closed agricultural production using artificial intelligence. The research focuses on analyzing modern AI technologies for microclimate management in greenhouses and vertical farms, evaluating their efficiency, advantages, and challenges of implementation. Additionally, practical examples of AI applications in the agricultural sector are examined, along with the prospects for the development of automated agrotechnologies. These innovations aim to enhance crop yields, optimize resource utilization, and ensure production stability in the face of climate change.
Keywords: кліматична система; агровиробництво